Location Probability Learning Requires Focal Attention. (April 2014) - Kabata, Takashi; Yokoyama, Takemasa; Noguchi, Yasuki; Kita, Shinichi
Target identification is related to the frequency with which targets appear at a given location, with greater frequency enhancing identification. This phenomenon suggests that location probability learned through repeated experience with the target modulates cognitive processing. However, it remains unclear whether attentive processing of the target is required to learn location probability. Here, we used a dual-task paradigm to test the location probability effect of attended and unattended stimuli. Observers performed an attentionally demanding central-letter task and a peripheral-bar discrimination task in which location probability was manipulated. Thus, we were able to compare performance on the peripheral task when attention was fully engaged to the target (single-task condition) versus when attentional resources were drawn away by the central task (dual-task condition). The location probability effect occurred only in the single-task condition, when attention resources were fully available. This suggests that location probability learning requires attention to the target stimuli.